2020
DOI: 10.21203/rs.3.rs-74772/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrospective Analysis of Real-World Treatment Patterns and Clinical Outcomes in Patients With Advanced Non-Small Cell Lung Cancer Starting First-Line Systemic Therapy in the United Kingdom

Abstract: Background: The treatment landscape for advanced non-small cell lung cancer (aNSCLC) has evolved rapidly since immuno-oncology (IO) therapies were introduced. This study used recent data to assess real-world treatment patterns and clinical outcomes in aNSCLC in the United Kingdom. Methods: Electronic prescribing records of treatment-naive patients starting first-line (1L) treatment for aNSCLC between June 2016 and March 2018 (follow-up until December 2018) in the United Kingdom were assessed retrospectively. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Published studies evaluating treatment patterns for aNSCLC describe a shift in treatment modalities that supports rapid acceptance and clinical uptake of ICIs immediately following their approval and incorporation into guidelines [13][14][15][16][17]. The current study showed that these shifts to ICIs have been maintained.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Published studies evaluating treatment patterns for aNSCLC describe a shift in treatment modalities that supports rapid acceptance and clinical uptake of ICIs immediately following their approval and incorporation into guidelines [13][14][15][16][17]. The current study showed that these shifts to ICIs have been maintained.…”
Section: Discussionsupporting
confidence: 60%
“…Characterizing the treatment landscape advances our understanding of how these therapies are used in real-world clinical settings, and could potentially inform management strategies to enhance patient outcomes. While several studies have reported patterns of firstline treatment for aNSCLC subsequent to ICI approval [13][14][15][16][17], these studies did not stratify by PD-L1 expression level and covered only the initial years after the introduction of ICIs and thus may not reflect contemporary management of patients with aNSCLC. Therefore, the objective of this study was to describe the treatment landscape and trends among patients with aNSCLC initiating first-line treatment across PD-L1 expression levels and those not undergoing PD-L1 testing.…”
Section: Introductionmentioning
confidence: 99%
“…A frequency of cytotoxic chemotherapy use in patients with metastatic lung cancer receiving systemic therapy follows previously published data from Australia, 31 the US, 20 and the United Kingdom. 32 Our older cohort, however, received less systemic therapy (50%) for advanced lung cancer when compared to younger cohorts; for example, Ngo et al reported receipt of systemic therapy in 76% and 65% of patients aged <60 and 60-69 years, respectively. 31 While only six ACTS participants (8%) received immunotherapy compared to 12% of similar patients in the US, 20 it should be noted that immunotherapy was not routinely used during the ASPREE time period (pre-2017).…”
Section: Discussionmentioning
confidence: 67%